2021
DOI: 10.34172/ijmpes.2021.04
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Monomycin and Gentamycin Sulfate on Growth of Promastigotes of Leishmania Under In Vitro Conditions

Abstract: Introduction: Given the prevalence of leishmaniasis in some parts of Iran and the medical problems caused by it and considering some reports on the effectiveness of monomycin in treating the disease, this study was performed to determine the effect of this drug on Leishmania major promastigotes in vitro. Materials and Methods: The study was conducted experimentally. Drug films containing 15% monomycin sulfate and 0.5% gentamicin sulfate were prepared using ethyl cellulose and hydroxypropyl methyl cellulose (HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…At the same time, there is no significant difference in the specific and separate presence of these antigens, but all of them have a Naini investigated the initial response of T cells in the secretion of IL-4 and found that the concentration of IL-4 is low in the early stages (35)(36)(37). It is necessary to induce a complete protective response through a carrier molecule that activates the cellular immune system and to use it with a molecule that stimulates the activity of macrophages in the body (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there is no significant difference in the specific and separate presence of these antigens, but all of them have a Naini investigated the initial response of T cells in the secretion of IL-4 and found that the concentration of IL-4 is low in the early stages (35)(36)(37). It is necessary to induce a complete protective response through a carrier molecule that activates the cellular immune system and to use it with a molecule that stimulates the activity of macrophages in the body (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Such information could also offer priceless insights into how parasites and hosts interact (71)(72)(73). New approaches to designing and manufacturing innovative epitope-based vaccinations have been made possible by increased bioinformatic tool expertise and advancements in recombinant DNA technology (74)(75)(76). The least immunogenic component of any antigenic determinant (epitope) can elicit a particular immune response (77)(78)(79).…”
Section: Epitope-based Vaccinementioning
confidence: 99%
“…A combination of DNA vaccines and cysteine protease I and II vaccines was used in dogs against L. infantum and resulted in remarkable prevention in these animals (37,38).…”
Section: Deris Et Almentioning
confidence: 99%